2020
DOI: 10.2147/ppa.s262578
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Characteristics and Patient-Reported Outcomes of Primary Care Physiotherapy in Patients with Whiplash-Associated Disorders: A Longitudinal Observational Study</p>

Abstract: Background: Whiplash-associated disorders (WADs) constitute a state of health characterized by a wide diversity of symptoms as a result of impairments of functions, activity limitations, and participation restrictions. Patient-reported outcome measurements (PROMs) and patient-reported outcomes (PROs) seem appropriate when describing and evaluating the health status of patients with WAD. Aim: To measure the use of PROMs and PROs as quality indicators in clinical reasoning, and to analyze and evaluate pre-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the population are summarized in Table 3 . Age, sex, and gender were not available for four studies [ 19 , 27 , 31 , 48 ]; seven studies did not provide additional details regarding the type and location of musculoskeletal disorder [ 19 , 27 , 28 , 31 , 32 , 36 , 43 ], while seventeen studies did not specify pathology onset [ 9 , 18 , 19 , 26 , 27 , 28 , 29 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RECORD statement is a checklist of items, including codes to identify participants and to classify patient characteristics, exposures, confounders and outcomes. Most items covered by the RECORD statement were included in our observational studies using RCD in patients with WAD ( 40 , 42 ). We anticipate that the RCD underlying our observational study could plausibly act as preliminary real-world evidence concerning (manual) physiotherapy management and WAD, and could be used to improve the design of future data-driven clinical improvement studies' ( 76 , 77 ).…”
Section: Suitability Of Routinely Collected Data For Quality Evaluati...mentioning
confidence: 99%
“…Health problems of patients with (chronic) WAD are often complex and multidimensional and require a particular clinical intuition based on a particular pattern recognition. Clinical intuition has been described as an outcome of interactions between a particular clinician or group of clinicians and a particular patient or patient group in a specialized setting [ 51 ].…”
Section: Introductionmentioning
confidence: 99%